Laparoscopic versus open pancreas resection for pancreatic neuroendocrine tumours: a systematic review and meta‐analysis. Issue 5 (7th November 2013) - Drymousis, Panagiotis; Raptis, Dimitri A.; Spalding, Duncan; Fernandez‐Cruz, Laureano; Menon, Deepak; Breitenstein, Stefan; Davidson, Brian; Frilling, Andrea
Abstract Background Over the last decade laparoscopic pancreatic surgery (LPS) has emerged as an alternative to open pancreatic surgery (OPS) in selected patients with neuroendocrine tumours (NET) of the pancreas (PNET). Evidence on the safety and efficacy of LPS is available from non‐comparative studies. Objectives This study was designed as a meta‐analysis of studies which allow a comparison of LPS and OPS for resection of PNET. Methods Studies conducted from 1994 to 2012 and reporting on LPS and OPS were reviewed. Studies considered were required to report on outcomes in more than 10 patients on at least one of the following: operative time; hospital length of stay (LoS); intraoperative blood loss; postoperative morbidity; pancreatic fistula rates, and mortality. Outcomes were compared using weighted mean differences and odds ratios. Results Eleven studies were included. These referred to 906 patients with PNET, of whom 22% underwent LPS and 78% underwent OPS. Laparoscopic pancreatic surgery was associated with a lower overall complication rate (38% in LPS versus 46% in OPS; P < 0.001). Blood loss and LoS were lower in LPS by 67 ml (P < 0.001) and 5 days (P < 0.001), respectively. There were no differences in rates of pancreatic fistula, operative time or mortality. Conclusions The nature of this meta‐analysis is limited; nevertheless LPS for PNET appears to be safe and is associated with a reduced complication rate and shorter LoS than OPS.